The Role of Internal Communication in Enhancing Employee Performance. A Case Study of Graphic Communication - Aklorbortu, Priscilla Makafui Adzo (UniMAC - GIJ, 2020)
Organizations can operate successfully, only if effective organizational communication takes place. One major component of organizational communication is internal communication. Internal communication is important for the successful functioning of organizations having various departments as it plays a massive role in organizational development. Internal communication binds the entire communication together and allows employees of various departments to work cooperatively to meet organizational goals. The main aim of this paper was to explore the role internal communication plays in improving employee performance. The discussion was based on series of empirical studies of communication and employee performance. The study shows that internal communication contributes to effective flow of information among employees within an organization, increases trust among employees and management as well as improves employees understanding of organizations and its products, ethics, culture and external environment. Internal communication also contributes significantly to career development of employees. However, the study noted some challenges to an effective internal communication in organizations and thus recommends that it is important for organizations to pay critical attention to internal communication as it influences not just employee performance but overall organizational performance. This is because, internal communication is necessary to monitor company operations, positive job performance and sustain ethical and behavior issues of employees making them dedicated and loyal for implementing outstanding performance to fulfill mission and vision of organization.
THESIS